(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the perilous outcomes of takfir – the act of declaring fellow Muslims as disbelievers – by individuals or groups who, after limited study, consider themselves "mujtahids" and hastily excommunicate others. It highlights how such actions, often perpetrated by certain sects and movements, embolden their followers to make audacious judgments on matters of faith and disbelief. Consequently, some of our youth, lacking profound Islamic knowledge, blindly follow these factions, leading them astray into misguidance and ignorance. The article addresses pressing questions: Why is this happening? Where do their errors lie? Is there a solution to this problem?